2021
DOI: 10.1002/onco.13933
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Cancer Survivors with Chemotherapy-Induced Peripheral Neuropathy: A Randomized Clinical Trial

Abstract: Background. Chemotherapy-induced peripheral neuropathy (CIPN) is a common, debilitating adverse effect of neurotoxic chemotherapy that significantly worsens cancer survivors' quality of life. Materials and Methods. Solid tumor survivors with persistent moderate-to-severe CIPN defined as numbness, tingling, or pain rated ≥4 on an 11-point numeric rating scale (NRS) were randomized in a 1:1:1 ratio to eight weeks of real acupuncture (RA) versus sham acupuncture (SA) versus usual care (UC). We previously reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 34 publications
1
62
0
Order By: Relevance
“…The present study examined two CIM intervention groups, treated with either acupuncture alone (group A) or a multimodal regimen combining acupuncture with other CIM therapies (group B). Although others, such as Bao et al, 29,30 compared true vs placebo/sham acupuncture for CIPN-related symptoms, the present study compared two true interventions, an approach more reflective of real-life clinical IO practice. 31,32 Although the findings do not suggest a significant difference between the two intervention subgroups, several differences are worth noting.…”
Section: Discussionmentioning
confidence: 99%
“…The present study examined two CIM intervention groups, treated with either acupuncture alone (group A) or a multimodal regimen combining acupuncture with other CIM therapies (group B). Although others, such as Bao et al, 29,30 compared true vs placebo/sham acupuncture for CIPN-related symptoms, the present study compared two true interventions, an approach more reflective of real-life clinical IO practice. 31,32 Although the findings do not suggest a significant difference between the two intervention subgroups, several differences are worth noting.…”
Section: Discussionmentioning
confidence: 99%
“…We included studies with at least one outcome measure. The severity of neurotoxicity and associated dysfunction was evaluated on the Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity (FACT/GOG-Ntx), which is used to assess sensory, motor, and hearing impairments associated with neuropathy ( 23 ). Ratings range from 0 to 44 points.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to the poor quality of the included studies, the conclusions need further substantiation. Recently, three high-quality randomized controlled trials (RCTs) on acupuncture for CIPN treatment have been reported (22)(23)(24). Two studies revealed that, compared with placebo acupuncture, acupuncture does not reduce chemotherapyinduced neurotoxicity and functional disability (22,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 5 RCTs investigated the effectiveness of treatment on numbness in 566 cancer survivors (24,31,33,39,58).…”
Section: Meta-analysis For Numbnessmentioning
confidence: 99%